2021
DOI: 10.1186/s12872-021-02379-7
|View full text |Cite
|
Sign up to set email alerts
|

ABCA1 and ABCG1 DNA methylation in epicardial adipose tissue of patients with coronary artery disease

Abstract: Background Recent studies have focused on the potential role of epicardial adipose tissue (EAT) in the development of coronary artery disease (CAD). ABCA1 and ABCG1 transporters regulate cell cholesterol content and reverse cholesterol transport. We aimed to determine whether DNA methylation and mRNA levels of the ABCA1 and ABCG1 genes in EAT and subcutaneous adipose tissue (SAT) were associated with CAD. Methods Paired EAT and SAT samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Besides, CAD with concomitant carotid artery disease or peripheral artery disease was accompanied by decreased ABCA1 gene expression in EAT, indicating that the process of reverse cholesterol transport may be also impaired in EAT of CAD patients. 47 Our study has some potential limitations. First, the number of patients was rather small, nevertheless, it must be taken into account the difficulty to obtain human EAT samples; besides, rigorous exclusion criteria were applied.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Besides, CAD with concomitant carotid artery disease or peripheral artery disease was accompanied by decreased ABCA1 gene expression in EAT, indicating that the process of reverse cholesterol transport may be also impaired in EAT of CAD patients. 47 Our study has some potential limitations. First, the number of patients was rather small, nevertheless, it must be taken into account the difficulty to obtain human EAT samples; besides, rigorous exclusion criteria were applied.…”
Section: Discussionmentioning
confidence: 88%
“…Besides, CAD with concomitant carotid artery disease or peripheral artery disease was accompanied by decreased ABCA1 gene expression in EAT, indicating that the process of reverse cholesterol transport may be also impaired in EAT of CAD patients. 47…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the atheromatous process in patients with CAD occurring in the coronary arteries, where the closest adipose tissue is the EAT. In addition, it has been reported that ABCA1 mRNA expression is influenced by risk factors such as smoking, age, diet and obesity ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both gene mutations in ABCA1 and DNA methylation modifications lead to this mRNA transcription deficiency. Previous reports have revealed a relationship between ABCA1 promoter region methylation and CHD risk [ 251 , 252 , 253 , 254 , 255 ]. Infante, et al [ 256 ] reported that ABCA1 , TCF7 , NFATC1 , PRKCZ , and PDGFA DNA are highly methylated in the CD4+ and CD8+ T cells of patients with acute coronary syndrome (ACS) using epigenome-wide analysis [ 256 ].…”
Section: Abca1 and Cardiovascular Diseasesmentioning
confidence: 99%